2014
DOI: 10.1007/s12038-014-9443-y
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus types 1 and 2 modulate autophagy in SIRC corneal cells

Abstract: Autophagy and apoptosis function as important early cellular defense mechanisms in infections and other diseases. The outcome of an infection is determined by a complex interplay between the pathogenic microorganism and these intracellular pathways. To better understand the cytopathogenicity of Herpes simplex virus types 1 and 2 (HSV-1 and -2), we studied the effect of these viruses on the autophagic and apoptotic processes in the SIRC corneal cell line. Infection with the KOS strain of HSV-1 and a wild-type s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Induction of autophagy by HSV-1 in THP-1 cells involved MyD88, since infection of MyD88-deficient cells does not trigger autophagy. Infection of rabbit corneal cells by HSV-1, but also by HSV-2 leads also to an activation of autophagy, which could be protective against apoptosis [ 69 ]. HSV-1 and HSV-2 are closely related viruses sharing around 50% of sequence identity.…”
Section: Autophagy Subversion By Herpesvirusesmentioning
confidence: 99%
“…Induction of autophagy by HSV-1 in THP-1 cells involved MyD88, since infection of MyD88-deficient cells does not trigger autophagy. Infection of rabbit corneal cells by HSV-1, but also by HSV-2 leads also to an activation of autophagy, which could be protective against apoptosis [ 69 ]. HSV-1 and HSV-2 are closely related viruses sharing around 50% of sequence identity.…”
Section: Autophagy Subversion By Herpesvirusesmentioning
confidence: 99%
“…However, the related antiviral mechanism of JZ-1 is not fully understood and needs further explanation. Recent studies have shown that HSV-2 blocks autophagic flux but host cells increase autophagy levels to inhibit viral infection in the later stages of the viral replication cycle (Kristen et al, 2015;Petrovski et al, 2014). Therefore, this study explored the underlying mechanisms of JZ-1 in treating HSV-2 infection by inducing autophagy.…”
Section: Jz-1mentioning
confidence: 99%
“…HSV-1 is able to prolong cell survival by autophagic resistance to apoptosis via the non-dependent mTOR pathway [ 115 ]. In addition, HSV-1 and HSV-2 infection of SIRC cells inhibited the occurrence of autophagy to increase the number of apoptotic cells, indicating that autophagy could resist the occurrence of apoptosis [ 116 ](121). Autophagy formation was detected in VZV-infected MRC-5 cells before 72 hours of infection, and a high percentage of apoptosis occurred after 72 hours.…”
Section: The Roles Of Apoptosis Autophagy and Necroptosis In Alpha-hmentioning
confidence: 99%